Declining trend of HTLV-1 among organ/ tissue donors in Iranian Tissue Bank between 2014–2021 - Arash Letafati; Sayed Hamidreza Mozhgani; Mehdi Norouzi; Amir Aboofazeli; Zahra Taghiabadi; Negar Zafarian; Saba Seyedi; Elnaz Mohammad Jaberi; Sedigheh Poursaleh; Maryam Karami; Sheida Sarrafzadeh; Ahmadreza Sadeghi (Retrovirology)
Abstract Background Human T-cell Lymphotropic Virus type-1 (HTLV-1) infection is associated with serious disorders, including Adult T-cell Leukemia/Lymphoma (ATLL) and HTLV-1–associated myelopathy/tropical spastic paraparesis (HAM/TSP). In addition to sexual, vertical, parenteral, and blood transfusion, organ/tissue transplantation is considered as a transmission route of HTLV infection. Given the substantial risk of HTLV-1 transmission and the subsequent development of HAM/TSP (approximately 40%) in kidney transplant recipients, pre-transplant donor screening is crucial. The present study aimed to investigate the prevalence of HTLV-1 in potential organ/tissue donors referred to the Iranian Tissue Bank and Research Center (ITBRC). Materials and methods The study population was potential organ and/or tissue donors referred to ITBRC between 2014 and 2021, including two groups of brain death (potential donors of organs and/or tissues) and circulatory death donors (potential tissue donors from Iranian Legal Medicine Organization). Initial screening was performed using enzyme-linked immunosorbent assay (ELISA), and positive cases were confirmed for HTLV-1 infection with polymerase chain reaction (PCR). Results 111 out of 3,814 donors were positive for HTLV-1 (3%). The rate of positive tests between 2014 and 2017 was 6%, which was significantly higher than the positive tests percentage between 2017 and 2021 with 0.5% (P-value < 0.001). The rate of test positivity in females was 4% compared to 2% in males (P-value = 0.001). Furthermore, individuals diagnosed with brain death exhibited a significantly lower likelihood of HTLV-1 infection (0.2%) compared to cases with circulatory death (4%) (P-value < 0.001). Conclusion Considering the contraindication of organ/tissue donation from donors with HTLV-1 positive test, these findings give an insight into the prevalence of HTLV-1 among potential organ/tissue donors in Iran. Moreover, the higher prevalence of HTLV-1 infection in circulatory death donors from Iranian Legal Medicine Organization urges for cautious evaluation in these donors.